Evolution of the expression and regulation of the nuclear hormone receptor ERR gene family in the chordate lineage - Papadogiannis, V; Hockman, D; Mercurio, S; Ramsay, C; Hintze, M; Patthey, C; Streit, A; Shimeld, SM (Elsevier, 2023)
The Estrogen Related Receptor (ERR) nuclear hormone receptor genes have a wide diversity of roles in vertebrate development. In embryos, ERR genes are expressed in several tissues, including the central and peripheral nervous systems. Here we seek to establish the evolutionary history of chordate ERR genes, their expression and their regulation. We examine ERR expression in mollusc, amphioxus and sea squirt embryos, finding the single ERR orthologue is expressed in the nervous system in all three, with muscle expression also found in the two chordates. We show that most jawed vertebrates and lampreys have four ERR paralogues, and that vertebrate ERR genes were ancestrally linked to Estrogen Receptor genes. One of the lamprey paralogues shares conserved expression domains with jawed vertebrate ERRγ in the embryonic vestibuloacoustic ganglion, eye, brain and spinal cord. Hypothesising that conserved expression derives from conserved regulation, we identify a suite of pan-vertebrate conserved non-coding sequences in ERR introns. We use transgenesis in lamprey and chicken embryos to show that these sequences are regulatory and drive reporter gene expression in the nervous system. Our data suggest an ancient association between ERR and the nervous system, including expression in cells associated with photosensation and mechanosensation. This includes the origin in the vertebrate common ancestor of a suite of regulatory elements in the 3' introns that drove nervous system expression and have been conserved from this point onwards.